2013
DOI: 10.1371/journal.pone.0078751
|View full text |Cite
|
Sign up to set email alerts
|

Tumor Cell Death Mediated by Peptides That Recognize Branched Intermediates of DNA Replication and Repair

Abstract: Effective treatments for cancer are still needed, both for cancers that do not respond well to current therapeutics and for cancers that become resistant to available treatments. Herein we investigated the effect of a structure-selective d-amino acid peptide wrwycr that binds replication fork mimics and Holliday Junction (HJs) intermediates of homologous recombination (HR) in vitro, and inhibits their resolution by HJ-processing enzymes. We predicted that treating cells with HJ-binding compounds would lead to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
7
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 65 publications
2
7
0
Order By: Relevance
“…Furthermore, colonic histology and faecal microbiome analysis of the peptidetreated mice were unchanged relative to the sham and placebo-treated groups. These findings are consistent with previous reports that show no evidence of cytotoxicity in a variety of human cell lines and murine primary cells exposed to peptide at concentrations below 100 µM (Dey et al, 2013;Su et al, 2010).…”
Section: Discussionsupporting
confidence: 93%
“…Furthermore, colonic histology and faecal microbiome analysis of the peptidetreated mice were unchanged relative to the sham and placebo-treated groups. These findings are consistent with previous reports that show no evidence of cytotoxicity in a variety of human cell lines and murine primary cells exposed to peptide at concentrations below 100 µM (Dey et al, 2013;Su et al, 2010).…”
Section: Discussionsupporting
confidence: 93%
“…Additionally, colonic histology analysis of peptide-treated mice was unchanged relative to the sham and placebo-treated groups. These findings are consistent with previous reports that show no evidence of cytotoxicity in a variety of human cell lines and murine primary cells exposed to peptide at concentrations below 100µM (Dey et al, 2013;Su et al, 2010). Moreover the in vivo studies revealed that 50-65µM peptide pre-treatment of C. rodentium prior to infection of mice ameliorated any evidence of infection based on C. rodentium colonization levels, fecal scores, colonic histology, and visual observation of overall animal health.…”
Section: A! B! C!supporting
confidence: 92%
“…Cell viability was determined by the methylthiazolyl-diphenyl-tetrazolium bromide (MTT) assay as described previously [ 32 ]. Briefly, after stimulation of cells with various concentrations of peptides (1–25 μg/ml) in six-well plates for 48 h, MTT solution was added to each well.…”
Section: Methodsmentioning
confidence: 99%